Evaluasi Faktor Risiko Penyakit Tidak Menular Melalui Pemeriksaan Gula Darah, Asam Urat, Dan Kolesterol - Tamalsir, Dylan; De Lima, Filda V. I.; Abbas, Mutmainnah; Mus, Rosdiana; Latuperissa, Glorya Riana; Nurlina, Wa Ode (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
Non-communicable diseases (NCDs) are the leading causes of morbidity and mortality in Indonesia, with risk factors such as unhealthy diet, physical inactivity, and overweight or obesity. This study aimed to evaluate NCD risk factors through blood glucose, uric acid, and total cholesterol measurements in Negeri Leahari, Leitimur Selatan District, Ambon City. A cross-sectional design was used with a convenience sampling technique, involving 138 voluntarily participating individuals. Blood glucose, uric acid, and total cholesterol levels were measured using an AutoCheck device, while data on diet, physical activity, and body mass index were collected through questionnaires. The results showed that 30% of participants had blood glucose levels ≥200 mg/dL, 22% had hyperuricemia, and 26% had total cholesterol levels ≥200 mg/dL. The main contributing factors were unhealthy diet (58%), low physical activity (52%), and a high prevalence of overweight and obesity (38%). Analysis showed a significant relationship between low physical activity and high uric acid levels (p = 0.04), while the relationship between diet and cholesterol and blood glucose levels showed a tendency toward increase, although not statistically significant (p > 0.05). The prevalence of NCD risk factors in Negeri Leahari is relatively high, highlighting the need for education on healthy eating, promotion of adequate physical activity, and routine monitoring of blood glucose, uric acid, and cholesterol levels to reduce the risk of further complications.